(untitled) (Fiep Bulletin - online, 2014)
Abstract -This article intends to analyze the possible relations between the different forms of bibliographic production (the theory) that can be seen during the historic processes of a sportive modality. The Rhythmic Gymnastics, as a pointer to the level of development on the pedagogic use, in contrast with the progress of it’s competitive utilizations (the practice).